A CYPome-wide study reveals new potential players in the pathogenesis of Parkinson’s disease - Hartz, Philip; Fehlmann, Tobias; Wagenpfeil, Gudrun; Unger, Marcus Michael; Bernhardt, Rita (Frontiers in Pharmacology, 2023)
Genetic and environmental factors lead to the manifestation of Parkinson’s disease (PD) but related mechanisms are only rudimentarily understood. Cytochromes P450 (P450s) are involved in the biotransformation of toxic compounds and in many physiological processes and thus pre-destinated to be involved in PD. However, so far only SNPs (single nucleotide polymorphisms) in CYP2D6 have been associated with the susceptibility of PD. Our aim was to evaluate the role of all 57 human P450s and their redox partners for the etiology and pathophysiology of PD and to identify novel potential players which may lead to the identification of new biomarkers and to a causative treatment of PD. The PPMI (Parkinson’s Progression Markers Initiative) database was used to extract the gene sequences of all 57 P450s and their 3 redox partners to analyze the association of SNPs with the occurrence of PD. Applying statistical analyses of the data, corre-sponding odds ratios (OR) and confidence intervals (CI) were calculated. We identified SNPs significantly over-represented in patients with a genetic predisposition for PD (GPD patients) or in idiopathic PD (IPD patients) compared to HC (healthy controls). Xenobiotic-metabolizing P450s show a significant accumulation of SNPs in PD patients compared with HC supporting the role of toxic compounds in the pathogenesis of PD. Moreover, SNPs with high OR values (>5) in P450s catalyzing the degradation of cholesterol (CYP46A1, CY7B1, CYP39A1) indi-cate a prominent role of cholesterol metabolism in the brain for PD risk. Finally, P450s partici-pating in the metabolism of eicosanoids show a strong over-representation of SNPs in PD pa-tients underlining the effect of inflammation on the pathogenesis of PD. Also, the redox partners of P450 show SNPs with OR>5 in PD patients. Taken together, we demonstrate that SNPs in 26 out of 57 P450s are at least 5-fold over-represented in PD patients suggesting these P450s as new potential players in the pathogenesis of PD. For the first time exceptionally high OR values (up to 12.9) were found. This will lead to deeper insight into the origin and development of PD and may be applied to develop novel strategies for a causative treatment of this disease.